2016
DOI: 10.18632/oncotarget.8071
|View full text |Cite
|
Sign up to set email alerts
|

High leukocyte mtDNA content contributes to poor prognosis through ROS-mediated immunosuppression in hepatocellular carcinoma patients

Abstract: Compelling epidemiological evidences indicate a significant association between leukocyte mitochondrial DNA (mtDNA) content and incidence risk of several malignancies, including hepatocellular carcinoma (HCC). However, whether leukocyte mtDNA content affect prognosis of HCC patients and underlying mechanism has never been explored. In our study, leukocyte mtDNA content was measured in 618 HCC patients and its prognostic value was analyzed. Moreover, we detected the immunophenotypes of peripheral blood mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Previous studies have demonstrated the interaction between various immune cells giving rise to the change of the immunological environment contributes to the underlying association. It has been reported that patients with high leukocyte mtDNA copy number have had increased Tregs and decreased NK-cells in peripheral blood, and Tregs were considered as inhibiting anticancer immunity while NK cells served as immunosurveillant, suggesting the patients with high mtDNA copy number awere in the immunosuppressive state2155. Moreover, the previous study also showed patients with high plasma mtDNA copy number held lower plasma TNF-α and IFN-ɣ but higher TGF-β1 concentrations21.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have demonstrated the interaction between various immune cells giving rise to the change of the immunological environment contributes to the underlying association. It has been reported that patients with high leukocyte mtDNA copy number have had increased Tregs and decreased NK-cells in peripheral blood, and Tregs were considered as inhibiting anticancer immunity while NK cells served as immunosurveillant, suggesting the patients with high mtDNA copy number awere in the immunosuppressive state2155. Moreover, the previous study also showed patients with high plasma mtDNA copy number held lower plasma TNF-α and IFN-ɣ but higher TGF-β1 concentrations21.…”
Section: Discussionmentioning
confidence: 95%
“…After a thorough review of titles and abstracts by two investigators independently, 394 studies were excluded and the full texts of remaining 26 references have also been artificial retrieved for further identification. Finally a total of 20 retrospective studies comprising 5413 patients were included in our study and 18 studies were used for analysis16171819202122252627282930313233343536. Among the included studies for analysis, there were 16 studies recruited Asian patients while 2 studies recruited Caucasian patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, lower peripheral blood leukocyte mtDNA copy number was correlated with aggressiveness and fast progression of prostate cancer 14 . Also, high mtDNA copy number in peripheral blood may predict a poor prognosis for hepatocellular carcinoma 15 , glioma 16 , colorectal cancer 17 , and head and neck cancer 18 . Taken together, these results suggested that the alteration of mtDNA content might play complicated roles in tumorigenesis and progression in a cancer-specific manner.…”
mentioning
confidence: 99%
“…The underlying mechanisms has been partially investigated. Several previous studies have demonstrated that SSBP1 decrease or deletion may lead to chromosome instability [ 11 ], and eventually prompt tumorigenesis [ 27 ], conversely, overexpression of SSBP1 also may contribute to tumor initiation through increasing mtDNA replication, thus leading to greater energy supplying and enhanced immunosuppression to facilitate tumor growth [ 28 ]. Collectively, these researches highlighted the vital role of SSBP1 in tumor initiation and progression, making SSBP1 an attractive tumor biomarker.…”
Section: Discussionmentioning
confidence: 99%